Automated Content Moderation in a Brazilian Marketplace - Zandavalle, Ana Claudia; Nascimento, Victor do; Gadelha, Carolina; Gama, Tatiana; Zagatti, Fernando; Nildaimon, Lucas; Barbirato, João Gabriel Melo; Real, Livy (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
Clarifying doubts can become decisive when shopping on e-commerces platforms. Considering the relevance of user generated content, this work aimed to develop an internal hybrid system, composed of machine learning models along-side a rule-based module, to moderate customers’ questions and sellers’ answers in one of the biggest marketplaces in Brazil.